Social transformations in bifurcation fields of self-organizing systems: methodological and conceptual aspects - V. Popov, Vitaly; A. Muzyka, Oksana; D. Skudnova, Tatyana; A. Petrushenko, Svetlana; P. Agafonova, Tatyana; D. Lichman, Irina (International Journal of Engineering and Technology, 2018)
The article considers different methodological approaches to studying the modern society undergoing a process of transformation. The authors stipulate that the modern society should be considered in its dynamics as a society of social transformations; expound on the need for a correct and adequate semantic formulation of significant issues of non-linear development of the society within the frameworks of the philosophy of science and the social philosophy; demonstrate different levels of application of the concepts and semantic representations in the research into social transformations at the level of complex systems; and reveal that in the study of social transformations within a transitional society it is appropriate to state that the social synergetics allows modelling some aspects of the creative practical activity of a cognizing social actor. Specifics of the development of social transformations in bifurcation fields in the context of non-linear development of the society are identified and discussed.Â